World Bank Corporate Scorecard September 2013 : Integrated Results and Performance Framework - World Bank (Washington, DC, 2013)
Two ambitious goals guide World Bank Group actions: (i) ending extreme poverty by reducing the percentage of people living on less than $1.25 a day to 3 percent by 2030; and (ii) promoting shared prosperity by fostering income growth for the bottom 40 percent of the population in every country. The pursuit of these goals needs to be done in a sustainable manner that secures the long-term future of the planet and its resources, ensures social inclusion, and limits the economic burdens future generations will inherit. The World Bank Group is committed to supporting countries in the achievement of these goals with a combination of financing, knowledge, and convening services. The World Bank Corporate Scorecard provides information on the overall performance of the World Bank, as well as the results achieved by client countries, in particular on key global development objectives. The Corporate Scorecard facilitates strategic dialogue between Senior Management and the Board of Executive Directors on progress that has been made and on areas that need attention.